Viver (d)o mar. Narrativa visual da pesca tradicional em São Miguel do Gostoso – RN. - Silvia Helena Zanirato (Confins)
In this visual essay is focused the activity of a traditional fishing community in São Miguel do Gostoso, Rio Grande do Norte. It presents in correlation text, picture, photographs collected in the field that are arranged in a visual narrative, aimed at understanding and explaining the work process of the fishermen in its relationship with the sea.